(3efGgL GdacQ heHGgL GdYHQs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW , J (B718 (3g` s ((3MSf Hf CMeO GdbQTi GdTGaYi GdeJWHH HWQGHdS GdefUhQjI s)
(3ChdgG (B:s
(3GdMeO ddg HJjbf eG UfY heHOY eG Ndb GdPi , hHYO agPG Gdaf GdQGHY ef Gdafhf GdJi OGaY GdYbd ai JOhjfgG s
(3BNQgG (B:s
(3Je Gdaf GdQGHY ef cJGH eHGgL GdacQ hefGgL GdYHQ hHJeGeg Je GdcJGH HYhf Gddg hdWaI s
(3jMJhi Ydi ef Gdaf GdQGHY ai WHGFY GdMjhGf fSNI CNQis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B42s
Keywords: (3eJaQbGJs